EVALUATION OF ANTIBIOTIC SUSCEPTIBILITY PATTERNS OF BACTERIAL PATHOGENS IN CLINICAL SPECIMENS. : JPUMHS; 2025:15:01, 146 157. http://doi.org/10.46536/jpumhs/2025/15.01.608 - Shehnaz Bakhtiar1, Muhammad Tariq Hamayun Khan2, Fatima Muhammadi Burki3, Madeeha4, Amber Javaid5, Jawwad Ahmed6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: The prevalence of bacterial resistance to antibiotics has escalated in recent years. Resistance against Gram-negative bacteria (GNB) and Gram-positive bacteria (GPB) has been documented. OBJECTIVE: This study investigated the frequency, antibiotic susceptibility, and resistance mechanisms of clinical sample isolates from Department of Pathology.MATERIAL AND METHOD: This study investigated the frequency, antibiotic susceptibility, and resistance mechanisms of clinical sample isolates from Department of Pathology. Aseptically collected 793 bacterial isolates from wound swabs, urine, blood, central venous pressure line tips, and respiratory specimens to grow on CLED or Blood agar for 24 hours at 37°C. The isolate will be identified using microbiological methods after culture. RESULT: From wound samples, which included pus, swabs, and tissue, 237 bacterial isolates were identified: Enterococcus species (n=59, 24%), Enterobacterales (n=148, 62%), and Pseudomonas aeruginosa (n=30, 12%). The urine sample produced a uniform distribution and quantity of isolates. In blood and CVP line tip cultures, 168 bacterial isolates were detected, including Acinetobacter species (n=37, 22%), Enterobacterales (n=56, 33%), and Salmonella Typhi (n=75, 44%). Included were Escherichia coli (n=8, 5.2%), Acinetobacter species (n=46, 30%), Klebsiella pneumoniae (n=20, 13.2%), and Pseudomonas aeruginosa (n=77, 50%). Whereas Ciprofloxacin resistance varied from 65–68% across locations, pus swab and urine isolates were resistant to Penicillin (75%) and Ampicillin (97%). Respiratory samples were moderately resistant to Ciprofloxacin (65.2%) and Gentamicin (52.8%) but low to Polymyxin B (6.2%) and Tigecycline (13.7%). These results show extensive first-line antibiotic resistance and continued vulnerability to last-resort medicines. CONCLUSION: This study shows that diverse clinical specimens often resist common antibiotics. The effectiveness of last-resort medicines like Polymyxin B and Tigecycline shows their importance in treating multidrug resistant diseases.